2015
DOI: 10.1021/la503949b
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Approach to Investigate Self-Assembly of Telodendrimer Based Nanocarriers for Anticancer Drug Delivery

Abstract: Delivery of poorly soluble anticancer drugs can be achieved by employing polymeric drug delivery systems, capable of forming stable self-assembled nanocarriers with drug encapsulated within their hydrophobic cores. Computational investigations can aid the design of efficient drug-delivery platforms; however, simulations of nanocarrier self-assembly process are challenging due to high computational cost associated with the large system sizes (millions of atoms) and long time scales required for equilibration. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“… 23 We have demonstrated that the hydrophilic hydroxyl-rich surface of CA faces towards the aqueous PEG layer on the core-shell interface of PEG 5k CA 8 micelles to minimize the surface tension, therefore stabilizing the nanocarriers. 33 With this in mind, we developed another two versions of telodendrimers with the rational architecture design: i.e. the second generation (G2) of hybrid telodendrimers and the third generation (G3) of functional-segregated telodendrimers ( Figure 2B ) using CA as co-building blocks.…”
Section: Resultsmentioning
confidence: 99%
“… 23 We have demonstrated that the hydrophilic hydroxyl-rich surface of CA faces towards the aqueous PEG layer on the core-shell interface of PEG 5k CA 8 micelles to minimize the surface tension, therefore stabilizing the nanocarriers. 33 With this in mind, we developed another two versions of telodendrimers with the rational architecture design: i.e. the second generation (G2) of hybrid telodendrimers and the third generation (G3) of functional-segregated telodendrimers ( Figure 2B ) using CA as co-building blocks.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Luo, Nangia and co-workers backed the synthetic work with extensive modeling and achieved very high drug loadings paired with excellent therapeutic efficacy. [49][50][51] Börner and co-workers employed a high-throughput screening to find an improved drug loading for different cargo. [52][53][54] The driving forces considered relevant for drug incorporation are hydrophobic and electrostatic interactions, hydrogen bonding, π-π stacking and van der Waals forces.…”
Section: Introductionmentioning
confidence: 99%
“…Their models were validated with experimental synthesis and evaluations of nanocarrier library. Jiang, et al 94 employed multiscale modeling together with experiments to understand the building blocks’ role in telodendrimer self-assembly process. Recently, microchip device development has become another direction to simulate a tumor's microenvironment and test the effectiveness of NPs for targeted drug delivery 95,90 .…”
Section: Discussionmentioning
confidence: 99%